Photocatalytic degradation of methylene blue dye by ZnO nanoparticle thin films, using Sol–gel technique and UV laser irradiation - Diaa Atta; Hanan A. Wahab; M. A. Ibrahim; I. K. Battisha (Scientific Reports)
Abstract The focus of the current work is the study of the effect of the photo-catalytic activity of ZnO nanoparticles. The photocatalytic destruction of methylene blue dye, a common water contaminant, was used to assess the photocatalytic efficiency of the ZnO nanoparticles from its aqueous solution by using ZnO nanoparticles thin film under UV light and laser irradiation. Sol–gel methods prepared ZnO nanoparticle thin films. X-ray diffraction and a field-emitted scanning electron microscope were utilized to examine the structure of the produced ZnO nanoparticles. An extended characterization by laser-based fluorescence and UV–visible spectroscopic techniques. The effects of operational parameters such as photo-catalyst load and contact time on photocatalytic degradation of methylene blue were investigated. The recent study’s findings showed that irradiation with a UV laser increases with power density 25 µW/cm2, the photo-catalytic rate. The UV spectra show decay for the band at 664nm decreased and the concentration of M.B. in monomer form decayed to 26% of the original concentration in 24 h, while the band at 612 which is related to the dimer M.B. molecules was not affected. The laser irradiation did the same for monomer M.B. molecules in only 3 h, while the dimer decreased to 28% of its original concentration. The reaction mechanism has been discussed by molecular modelling. Quantum mechanical calculations at B3LYP/6-311g(d,p) level indicated that methylene blue changed from dimers to monomers in the existence of ZnO. The current results present a method for degrading M.B. not only in wastewater but also in the industrial waste scale.